DOES SUBJECT CHOICE IN A JOINT HONOURS DEGREE AFFECT HIGHLY SKILLED GRADUATE EMPLOYMENT? - Pigden, Louise; Moore, Garford (PUPIL: International Journal of Teaching, Education and Learning, 2017)
Joint or combined honours degrees in the UK generally permit students to study two subjects to full bachelors degree depth, by studying half the curriculum content of the respective equivalent single honours degrees. This affords students the opportunity to study a more diverse curriculum that they feel passionate about. However this is at the expense of breadth of study in each particular subject, which is a strong defining feature of the majority of UK single honours degrees. Does the decision to study certain subjects in a joint or combined honours degree affect the graduate’s subsequent highly skilled graduate employment? The literature is weak in examining this, either for joint honours subjects generally or for specific combinations of subjects. This paper presents an analysis of the UK Destination of Leavers from Higher Education survey between 2011/12 and 2014/15 at the level of the individual combinations studied – a national dataset which has not previously been critiqued in this particular way in the public domain. This analysis will determine whether certain combinations lend themselves to higher rates of highly skilled graduate employment, irrespective of other factors affecting employment, for example the characteristics of different universities. We conclude that subject choice greatly affects graduate employment, and we present recommendations around the preparedness or otherwise of graduates for highly skilled graduate employment, as determined by their choice of subjects to study.